Wood Loss Assessment in Forest of Sal (Shorea robusta) by Heart Rot of Central Terai of Nepal - Shankar Tripathi; Yojana Adhikari (International Journal of Forestry Research)
A significant volume of wood was lost due to wood defects; however, few studies were done to quantify wood loss by wood defects. This study was focused on quantifying wood loss by heart rot, especially hollowness in Shorea robusta. The study was conducted in Tileswornath community forest of Rautahat district. The data were collected from the felling site of the regeneration felling block of Tileswornath community forest. 44 trees were selected randomly, and tree diameter, total height, and volume were measured. The destructive method was followed as heart rot cannot be visible from the surface. Felled trees were sanctioned into 285 logs and separated based on the hollowness. Hollow diameters at both thin end and mid and thick end, as well as length, were measured on the hollow log, and Smalian’s formula was used to calculate the volume of hollowed portion, and volume calculation formula for the cylinder was used to calculate total volume. For the solid logs, mid diameter and length of the log were measured and volume calculation formula for the cylinder was used to calculate total volume. Logistic regression was performed to identify the relation of total height and diameter with the probability of hollowness presence. The study showed that 59% of sampled trees and 34.39% of logs were found to be hollowed due to heart rot. 41.79% volume was occupied by hollow on the hollowed log. Logistic regression discards the relation of height to the hollowness but signified the relation of diameter to the probability of hollowness presence. Before implementation of scientific forest management modality, the timber retained in stump per tree was found as 0.18 cubic feet.